The Inventio of Analogia between Rhetoric and Theology in Garnerius of Rochefort (c. 1140 - c. 1225) (Doctor Virtualis, 2023)
In the years stradding between the XII and XIII century, Cistercian Garnerius of Rochefort devoted himself to the composition of a short treatise, De contrarietatibus in Sacra Scriptura. The work, still unpublished, makes use of the sermocinal arts to resolve scriptural ambiguities. The prologue to De contrarietatibus reveals a peculiar interest of the Cistercian in the discipline of rhetoric and, in particular, in the use of tropes to understand the contents of Revelation. On closer inspection, however, Garnerius’ choice to resort to the refinement of the tools of rhetoric to illuminate the meaning of Scripture finds full justification only in light of his conception of natura and Scriptura as theophanies and/or symbols. Now in this symbolic horizon, of Neo-Platonic-Dionysian derivation, there always is a mechanism of translation at work, in res as well as in language, an extension of the word, beyond its ordinary content, to another meaning of a spiritual nature. So the rhetorical workmanship of biblical expressions assumes a cognitive, rather than merely ornamental, value because it is capable of manifesting, through a dialectical interplay of correspondences and/or ruptures, an analogical proportionality between the visible and the invisible.
Keywords: Rhetoric; Analogy; Biblical exegesis; Theophany; Neoplatonism